Independence of the dynamic grid of finite elements for the calculation of the aerodynamic resistance of linehaul trains - D.B. Beherskyi; I.V. Vitiuk; O.A. Levkivskyi; O.O. Bahinskyi; A.O. Koval (Технічна інженерія, 2025)
The article investigates the effect of changing the maximum size of the finite element of the dynamic grid on the accuracy of calculating the aerodynamic drag force of a linehaul train. The calculations were performed in the Ansys Fluent environment, which allows modeling air flows and their interaction with objects, in particular with a linehaul train.